(3QSGdI aj GdaUOs - (3CMeO Hf eMeO GdWHQj, CHh GdMSf,J (B366 (3g` s
(3ChdgG (B:s
(3GdMeO ddg hdi GdMeO GdeaUd Ydi LejY ef ai GdYGde Efi QCjJ CWHGLQLGf hbUGQFge jCJhf GdTF ef ZjQ JejjR s
(3BNQgG (B:s
(3hjLH Cf jchf GdEfSGf Ydi MPQ ef Cf jbY Ydjg TF ajfbU Ch jfaN KGfjkG aEf ajg NUQkG YXjekG hGddg jhabfG ddQTGO JeJ GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdSGHYIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(568) s
Keywords: (3GdWHs